2018
DOI: 10.1186/s12884-018-1972-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and management of pre-eclampsia and eclampsia in antenatal and labor and delivery services: findings from cross-sectional observation studies in six sub-Saharan African countries

Abstract: BackgroundPreeclampsia and eclampsia (PE/E) are major contributors to maternal and neonatal deaths in developing countries, associated with 10–15% of direct maternal deaths and nearly a quarter of stillbirths and newborn deaths, many of which are preventable with improved care. We present results related to WHO-recommended interventions for screening and management of PE/E during antenatal care (ANC) and labor and delivery (L & D) from a study conducted in six sub-Saharan African countries.MethodsFrom 2010 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 18 publications
(20 reference statements)
7
47
0
Order By: Relevance
“…Availability of levonorgestrel 750mcg, the emergency contraceptive, was for example low across the countries, and this finding is reflected in the trends of use [49][50][51][52]. Comparable to other studies, magnesium sulphate, critical in managing pre-eclampsia and eclampsia, also had a low availability in all countries, with an especially low availability in Zambia [28,53,54]. Medical devices also had a suboptimal availability: tubal ligation and vasectomy kits had a very low availability across the countries, while availability of ultrasound scans was shown to be variable, with a higher availability in Kenya's and Uganda's public sector than in Tanzania and Zambia.…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…Availability of levonorgestrel 750mcg, the emergency contraceptive, was for example low across the countries, and this finding is reflected in the trends of use [49][50][51][52]. Comparable to other studies, magnesium sulphate, critical in managing pre-eclampsia and eclampsia, also had a low availability in all countries, with an especially low availability in Zambia [28,53,54]. Medical devices also had a suboptimal availability: tubal ligation and vasectomy kits had a very low availability across the countries, while availability of ultrasound scans was shown to be variable, with a higher availability in Kenya's and Uganda's public sector than in Tanzania and Zambia.…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…Subnational budgets should prioritise paving roads from health posts to main roads, and additional interventions should be trialled, including strategically placed shared ambulances and maternity waiting homes adjacent to health centres and hospitals 22 68 69. Strengthening antenatal care would enable referral to higher-level facilities for women with preidentifiable conditions (including twin pregnancy and pre-eclampsia) 70–72. The extent of informal use of health services between Senegal and neighbouring Gambia is unknown; however, providers in Senegal are unable to refer to facilities in the Gambia, even if those are nearer: reciprocal formal arrangements between these countries for obstetric emergencies should be considered.…”
Section: Discussionmentioning
confidence: 99%
“… 50–52 Observations of WHO-recommended practices for screening of pre-eclampsia/eclampsia in six sub-Saharan African countries, similarly found that a low proportion of women admitted to labour and delivery services were asked about danger signs, but substantially more women (77%) had their blood pressure checked on admission. 51 Low implementation of evidence-based care measures during the initial assessment and postpartum period indicate potential missed opportunities to identify and manage complications, as evident in the referral cases. Referrals post partum and intrapartum included women with high-risk pregnancies such as severe pre-eclampsia/eclampsia, breech position and twins who should have been referred to a higher level of care.…”
Section: Discussionmentioning
confidence: 99%